Arbuscular mycorrhiza as a biofertilizer in production of coffee - Hernández-Acosta, Elizabeth; Trejo-Aguilar, Dora; Rivera-Fernández, Andrés; Ferrera-Cerrato, Ronald (REVISTA TERRA LATINOAMERICANA, 2020)
In coffee plantations in southeastern Mexico, the chemical, physical and biological degradation of soils affects the production of plants. This situation economically harms the coffee growers, so it is common to place the neglect of their plantations where the cultivation tasks such as pruning and fertilization are costly. To solve the problem of fertilization, the application of arbuscular mycorrhizal inocula is recommended, its effectiveness is clear in vegetables and fruit trees. The response of two inocula (Rhizophagus aggregatus) and the consortium formed by the fungi Glomus claroides, Rhizophagus diaphanus and Paraglomus albidum (CMgrp) was evaluated in the coffee varieties garnica, catimor, caturra and catuaí, with the purpose of locating the best symbiosis plant-fungus. The variables height of the plant, dry matter, content of phosphorus in leaves, percentage of mycorrhizal colonization, percentage of mycorrhizal eff iciency, percentage of phosphorus absorbed by mycorrhization and the eff iciency index of mycorrhizae in the health of the plant were evaluated. (Em) The results showed that the CMgrp consortium generated the highest values and increases with respect to non-inoculated plants in the plant height and dry matter variables (177 and 1701% for garnica variety) and phosphorus content (650% in the catimor variety). The response of the plants to mycorrhization showed the best results in the garnica varieties (34.32% colonization percentage) and caturra (1670% mycorrhizal eff iciency and 1651% phosphorus absorbed by mycorrhization effect). The Em index revealed that the coffee plants inoculated with the CMgrp presented better health. It is recommended to use the CMgrp consortium as a biofertilizer in coffee plants, to ensure the success of the transplant, a situation that will represent an economic and time saving for the coffee grower.